Surgical ablation of atrial fibrillation during mitral valve surgery: a systematic review and meta-analysis - Eranki, Aditya; Muston, Benjamin; Wilson-Smith, Ashley; Wilson-Smith, Christian; Williams, Michael; Doyle, Matthew; Misfeld, Martin (Annals of Cardiothoracic Surgery, 2024)
Background: Atrial fibrillation (AF) is a common tachyarrhythmia, affecting approximately 33 million people worldwide, and is frequently associated with mitral valve disease. Surgical ablation during mitral valve surgery provides an opportune circumstance for arrhythmia correction. The results of recent randomized trial data are promising, demonstrating both safety and efficacy. The aim of this systematic review is to report the efficacy and morbidity of concomitant surgical ablation for AF during mitral valve surgery.Methods: Five electronic databases were searched from inception to March 2023. All studies reporting the primary outcome, freedom from AF (FFAF), for patients with a history of AF undergoing concomitant mitral valve surgery were identified. Studies with patient cohorts less than 100 were excluded. Relevant data were extracted and a meta-analysis of proportions was conducted using a random-effects model. Survival data were pooled from original Kaplan-Meier curves and reconstructed, reporting aggregate FFAF and survival.Results: Thirty-six studies with a total of 8,340 patients were included in the systematic review. All 36 papers reported postoperative FFAF with a pooled result of 76.9% [95% confidence interval (CI): 73.8–79.9%] at a weighted mean follow-up of 40.2 months, however this result was associated with significant heterogeneity (I2=89%). A total of 31 studies reported postoperative short-term mortality, with a pooled result of 1.68% (95% CI: 1.15–2.29%). Aggregate survival at 1 to 5 years was 93.7%, 92.5%, 91.3%, 89.4%, and 87%, respectively, and aggregate FFAF for 1 to 5 years was 90.2%, 83.5%, 79.5%, 76.4% and 73.2%, respectively.Conclusions: Evaluation of the evidence suggests that concomitant ablation for AF during mitral valve surgery is both safe and efficacious. The results were associated with significant heterogeneity, reflective of variable institutional protocols, patient characteristics, and lesion sets. Randomized data with longer term follow-up would help validate these results.